Pengaruh Berbagai Konsentrasi Dimethylsulfoxide terhadap Kualitas Semen Beku Ayam Hutan Hijau Post Thawing - Bebas, Wayan; Laksmi, DND Indira (Veterinary Science and Medicine Journal, 2014)
The process of freezing and thawing on semen can lead to physical stress, often called cold shock, and couses the structural and biochemical damage that affecting cell function and ultimately lead to the death of the cell The aim of this study was to know the effect of the addition of various concentrations of dimethylsulfoxide (DMSO) as the intracellular cryoprotectant in phosphate yolk diluent on the post thowing quality of the green jungle fowl semen. The study used eight green jungle fowl semens which were collected with massage techniques. Semen was evaluated macroscopically and microscopically. Good quality semen was diluted with phosphate yolk which was added four different concentration of DMSO, namely 4%, 6%, 8%, and 10%. Semen was then filled and sealed in a mini straw (0.25 mL) with the concentration of 150.106 cells, and equilibrated at 4oC for 4 hours. The semen freezing was processed using conventional method. Evaluation was performed on post thawing semen. The evaluation of semen quality included the progressive motility and plasma membrane intact. Data were analyzed by analysis of variance. If there were any significant differences, the data were futher analyzed by Duncan test. The results showed that addition of DMSO concentration of 6% has resulted the progressive motility and intact plasma membrane higher significantly (P <0.05) than those of the addition of DMSO concentration 4%, 8%, and 10%.
Keywords: Dimethylsulfoxide, frozen semen quality, green jungle fowl